Critical approach to diatom-based bioassessment of the regulated sections of urban flowing water ecosystems. (September 2019) - Szczepocka, Ewelina; Żelazna-Wieczorek, Joanna; Nowicka-Krawczyk, Paulina
Highlights: Diatom indices faultily evaluated the ecological status of degraded urban streams. We explained the inaccuracies between the bioassessment and the actual state. The greatest influence on diatom communities had hydromorphological transformations. The stream transformations caused tremendous changes of habitat conditions. We showed that some dominant species disturb the bioassessment of ecological state. Abstract: Hydromorphological transformations of small urban streams results in changes in habitat conditions, i.e. increase in water speed current and/or oxygen concentration, and finally changes in aquatic organism structure. The ecological status of two regulated urban streams was determined by diatom-based biomonitoring in their upper and lower sections using selected diatom indices (IO, IPS, IBD, GDI, TDI). Qualitative and quantitative analyses were performed to analyse the structure of diatom assemblages and to reveal the spatial relationships between stream sites. The bioassessment was supported with a chemical analysis of the water. The upper sections were found to be characterised by poor/bad ecological status, and the lower sections below highly-transformed and impacted streambeds by good/moderate status. Since the bioassessment revealed unexpected results, an analysis was performed of the dominant species, with special attention paid to the autecology of diatoms. A new model of bioassessment was implemented where the most frequent and dominant species, Achnanthidium minutissimum, was excluded from the analysis. The results obtained by the new analysis were similar to those of the chemical analysis. Such a critical approach is needed to reveal the true ecological status of flowing water ecosystems, particularly in the case of regulated streams where transformation has resulted in a change in more 'pseudo-mountain' habitat conditions.